Social media, local justice and citizen-led digital policing - Hadjimatheou, Katerina (Criminological encounters, 2021)
Recent efforts by police to encourage citizens to take more responsibility for the security of their neighbourhoods and communities have contributed to the emergence of what is becoming known as 'citizen-led digital policing'. This article examines how the activities of these newly ‘responsibilised’ citizens poses a challenge to a model of security governance that relies on the maintenance of clear distinctions between authorised security agencies and those they protect, by blurring the lines between the police and the public, and between responsible citizens and dangerous and unaccountable vigilantes.